2020
DOI: 10.1038/s41598-020-58879-7
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination characteristics of invasive Spartina alterniflora Loisel in Japan: implications for its effective management

Abstract: Spartina alterniflora, intentionally or unintentionally introduced worldwide, has adversely impacted local Japanese ecosystems. Thus, prediction of future distributions of S. alterniflora and its management are required. Local population expansion after establishment depends heavily on asexual (clonal) reproduction, whereas sexual (seed) reproduction is one of the critical factors for estimating invasion success and the likelihood of colonization to new habitats. However, knowledge about the germination charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…It was found that number of shoots which indicated clonal growth increased slightly with temperature ( Liu et al, 2016 ). Our results show that germination responds positively to higher temperatures, with or without a period of cold stratification, consistent with previous studies ( Zhu et al, 2011 ; Hayasaka et al, 2020 ). In future climate scenarios, the increase with temperature on both clonal growth and sexual reproduction may lead to population expansion.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that number of shoots which indicated clonal growth increased slightly with temperature ( Liu et al, 2016 ). Our results show that germination responds positively to higher temperatures, with or without a period of cold stratification, consistent with previous studies ( Zhu et al, 2011 ; Hayasaka et al, 2020 ). In future climate scenarios, the increase with temperature on both clonal growth and sexual reproduction may lead to population expansion.…”
Section: Discussionsupporting
confidence: 93%
“…Results of the microsatellite analysis made it clear that some S. alterniflora individuals (St. 13,15,16,and 18) in the Tsuboi River (northern Kumamoto) had a heterozygous at only one locus, while two individuals growing sympatrically (St. 14 and 17) had a homozygous at all of the loci ( Supplementary Table 2). Spartina alterniflora rapidly spread their populations via both sexual (seed) (Hayasaka et al, 2020) and asexual (clonal) reproduction and then form a high-density single colony (Somers and Grant, 1981;Davis et al, 2004). It is suggested that although these individuals have actually grown via seed propagation (i.e., sexual reproduction), they may be considered as clones with exactly the same genotype due to the extreme homozygosity.…”
Section: Genetic Relationships Between Japanese Spartina Alternifloramentioning
confidence: 99%
“…The production of the seeds expected 5176 seeds/m 2 by our data, the total seed production of the area would be over 2500000 seeds. Hayasaka (2020) reported the percentage of the seeds is almost 60% then 1300000 seeds dispersed in 2020. The invasive ability is serious problems [14].…”
Section: Discussionmentioning
confidence: 99%
“…Hayasaka (2020) reported the percentage of the seeds is almost 60% then 1300000 seeds dispersed in 2020. The invasive ability is serious problems [14]. In 2016 5 km away from this area, single population was observed in Agui River, near sea shore.…”
Section: Discussionmentioning
confidence: 99%